Peran Majelis Agama Islam Thailand dalam Penerbitan Sertifikat Halal Food di Thailand - Poramint Chaikong; Safitri Mukarromah (Proceedings Series on Social Sciences & Humanities, 2022)
This study aims to determine the role of the Thai Islamic Religious Council in the Process of Giving Halal Certificates to Food and Beverage Products and the obstacles faced in the process of granting halal certificates. This research is a type of field research with a descriptive qualitative approach. The data obtained are in the form of primary data sources and secondary data. Data collection techniques using interviews, observation, and documentation. The data collected will be analyzed qualitatively using a qualitative descriptive method. The results showed that the role of the Thai Islamic Religious Council in the Process of Giving Halal Certificates to Food and Beverage Products, had complied with the provisions of the Thai Islamic Religious Council or MAIT. MAIT is an institution in fostering the participation of Muslims in Thailand. The Thai Islamic Religious Council in determining the standardization of halal food products by checking the company's location, logo and halal certificate in Thailand, making stamps on halal food products in Thailand.